(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Pseudo-exfoliation is an age-related systemic disorder characterized by deposition of abnormal fibrillar material on ocular tissues, leading to poor pupillary dilatation, zonular weakness, and increased risk of complications during cataract surgery. Cataract extraction in PXF eyes is therefore considered surgically challenging. The present study was undertaken to evaluate the visual outcome of cataract surgery in patients with pseudoexfoliation and to analyze associated intraoperative and postoperative complications. Methods: This hospital-based observational study was conducted in the Department of Ophthalmology, People’s College of Medical Sciences and Research Centre, Bhopal, over 18 months. A total of 58 patients aged ≥50 years with senile cataract associated with pseudoexfoliation were included. Detailed preoperative evaluation included BCVA (Best-Corrected Visual Acuity), intraocular pressure measurement, gonioscopy, slit-lamp examination, and cataract grading. All patients underwent SICS (Small Incision Cataract Surgery). Patients were followed postoperatively on day 1, day 3, and at 1 month for visual outcomes and complications. Results: The mean age of patients was 68.16 ± 11.70 years, with slight male predominance (51.72%). Poor pupillary dilatation was observed in 36.21% of cases. Intraoperative complications included zonular dialysis (6.8%), posterior capsule rupture (5.1%), vitreous loss (3.4%), and aphakia (1.7%). Early postoperative complications included corneal edema (32.76%), iritis (32.76%), raised intraocular pressure (24.14%), hyphema (8.62%), retained lens matter (5.17%), and IOL decentration (6.90%). At 1 month postoperatively, 91.38% of eyes achieved visual acuity between 6/6 and 6/12. Zonular dialysis showed a significant association with posterior capsule rupture (p < 0.0001). Conclusion: Pseudoexfoliation significantly increases the complexity of cataract surgery because of poor mydriasis and zonular instability. Careful preoperative evaluation, meticulous surgical technique, and appropriate postoperative management can achieve satisfactory visual outcomes, despite higher intraoperative and postoperative complication rates.